Кримінологічні засади протидії злочинам агресії - Сокуренко, В. В.; Sokurenko, V. V.; Valerii Sokurenko (Вісник Кримінологічної асоціації України. - 2016. - № 3 (14). - С. 11-21, 2016)
Стаття присвячена характеристиці кримінологічних засад протидії злочинам агресії. Встановлено, що вони складають систему міждисциплінарних наукових начал, підходів, керівних положень в організації, розробці та реалізації заходів щодо ранньої, безпосередньої та посткримінальної превенції, які ґрунтуються на кримінологічних знаннях про детермінацію, закономірності відтворення злочинів агресії, механізм злочинної поведінки, особистість злочинця. У структурі кримінологічних засад запропоновано розглядати кілька базових взаємопов’язаних їх компонентів: орієнтуючий, структурний та функціональний. Надано їх характеристику.

The article is focused on criminological principles of counteracting crimes of aggression. It has been established that they form a system of interdisciplinary scientific principles, approaches, guidelines in the organization, development and implementation of measures for early, direct and post-criminal prevention, based on criminological knowledge on determination, the normality of reproduction of crimes of aggression, the mechanism of criminal behavior, offender’s personality. The author has suggested to consider within the structure of criminological principles, a few basic interrelated their components: orienting, structural and functional. Orienting component of criminological principles of counteracting crimes of aggression appears as axiological (value-worldview) and teleological (target) base of criminal and preventive activity. It has a long history of development and currently is characterized by an extensive network of humanistic and liberal guidelines and principles. It has been emphasized on the fact that we have to consider the nearest perspective of bringing the establishment of liberal and humanist dominant through the concept of non-violence within public administration at the local, national, regional and global levels as a general purpose in the structure of orienting component of criminological principles of counteracting crimes of aggression. In the future, it has to find its details in the cascade of tactical tasks, the specific list and sequence of the implementation of which will depend on the political and economic conditions, environmental and criminological situation. Structural elements of counteracting crimes of aggression include: legal, resource bases, the system of subjects of general and special prevention. Special attention is paid on the need to develop international and legal mechanisms to overcome the veto to enable UN functions to be fully implemented. Functional elements of the system of counteracting crimes of aggression are its dynamic components and ensure the implementation of the capacity of structural components according to their destination, status, the actual abilities. These elements include levels, areas and specific measures of criminal and preventive activity. Among the levels, we allocate national, regional and global. Among areas we distinguish the following: ensuring stability of economic growth; formation of foreign accounts payable, as well as parameters of information security of the country taking into account the provisions of the Military Doctrine of Ukraine; monitoring, political and legal stabilization of the situation of domestic and foreign policy, taking into account the forecasts of military and political risks and their projection on the political situation of national, regional and global levels; reforming the educational system based on the restoration of historical truth, combating falsification, stimulation of national memory, respect and honor to the Ukrainian statehood. The measures of counteraction include economic, legal, political, cultural and psychological ones.

Статья посвящена характеристике криминологических основ противодействия преступлениям агрессии. Установлено, что они составляют систему междисциплинарных научных начал, подходов, руководящих положений в организации, разработке и реализации мер ранней, непосредственной и посткриминальной превенции, которые опираются на криминологические знания о детерминации, закономерностях воспроизводства преступлений агрессии, механизме преступного поведения, личности преступника. В структуре криминологических основ предложено рассматривать несколько базовых взаимосвязанных их компонентов: ориентирующий, структурный и функциональный. Дана их характеристика.
Criminological principles of counteracting crimes of aggression
Криминологические основы противодействия преступлениям агрессии
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; злочини агресії; протидія злочинності; агресія; рівень злочинності; уровень преступности; напрями протидії злочинності; crimes of aggression; counteraction; criminological principles; level; противодействие преступности; combating crime; преступления агрессии; aggression; агрессия